8A.003 Drivers who cause serious injury – can we target behaviour change?. (14th March 2021) - Nunn, James; Barnes, Jo; Petherick, Emily; Morris, Andrew
Abstract : Background: Road safety campaigns tend to be nationally focussed, targeting all drivers, however these are general and often ineffective in reaching drivers causing serious road injury collisions. This study aimed to identify culpable drivers involved in collisions and consider the potential of delivering focused road safety campaigns to reduce serious injury on the roads. Methods: This study linked UK police data (STATS19) with hospital trauma data from the Trauma Audit Research Network (TARN) to identify serious (MAIS3+) injury collisions and the drivers involved for the county of Cambridgeshire (UK). These drivers were then assessed to be culpable, contributory or non-culpable for the serious injury collision. Additionally, geodemographic profiles were identified for the drivers using ACORN (A (UK) Classification of Residential Neighbourhoods) to establish if culpable drivers differed from non-culpable drivers. ACORN uses postcodes to differentiate areas by wealth (6 categories), available money (18 groups) and household description (62 types). Results: A total of 399 Cambridgeshire drivers were profiled, with 276 drivers considered culpable or contributing to the collision and 123 non-culpable. The ACORN categories and groups for the proportions of culpable and non-culpable drivers were similar. However, within the household types differences existed with culpable drivers having higher proportions of semi-skilled workers living in traditional neighbourhoods. In contrast non-culpable drivers had higher proportions of larger families living in rural areas. Conclusion: The findings suggest there are differences in specific household types. Using additional marketing tools, targeted road safety education campaigns could be aimed at culpable drivers living in these households